Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1097/scs.0000000000001777
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Variant of Calcifying Epithelial Odontogenic Tumor

Abstract: To the Editor: The calcifying epithelial odontogenic tumor (CEOT) is an uncommon benign tumor of epithelial origin, representing <1% of all odontogenic tumors. Among the histological variants of CEOT, the true cystic variant of CEOT is extremely rare, with only 3 welldocumented cases reported in the English-language literature. [1][2][3] In this report, we describe the clinical, radiographic, and histopathological features of a case of cystic variant of CEOT.A 22-year-old male patient was referred to evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The lesion was enucleated. A number of similar cases have been reported [48][49][50], and subsequently, a microcystic variant has also been described [25]. In this lesion, a pseudo-glandular appearance was reported in association with otherwise rather conventional CEOT histology.…”
Section: Cystic/microcystic Variantmentioning
confidence: 52%
“…The lesion was enucleated. A number of similar cases have been reported [48][49][50], and subsequently, a microcystic variant has also been described [25]. In this lesion, a pseudo-glandular appearance was reported in association with otherwise rather conventional CEOT histology.…”
Section: Cystic/microcystic Variantmentioning
confidence: 52%
“…Interestingly, all cystic CEOT cases showed gross expansion of cortical bone, average size was 3.3 cm in the greatest diameter. To the best of our knowledge, our case is the second microcystic variant of CEOT reported [13].…”
Section: Discussionmentioning
confidence: 73%
“…In 2006, Gopalakrishnan et al reported the first case of cystic variant of CEOT in a 15-year-old male with an expansive mixed lesion of the posterior maxilla [10]. Since then, only three additional CEOT cases showing considerable cystic or microcystic pattern have been reported [11][12][13]. All patients were males with a median age of 24.5 years (ranging from 15 to 31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations